THEORETICAL SUBSTANTIATION OF А PRIMARY SCHOOL TEACHERS TRAINING SYSTEM TO USE THE ELECTRONIC LINGUOMETHODICAL TOOLS IN THEIR PROFESSIONAL ACTIVITY - Khyzhnyak, Inna A. (Educological discourse, 2017)
The important role of primary school teachers systemic training to use the electronic linguomethodical tools in professional activities is substantiated in the article. The author analyzes the existing primary school teachers professional training experimental system, summarizes its building ways and on this basis formulates the own definition of the primary school teachers training how to use the electronic linguomethodical tools in professional activities, describes its construction, which consists of traditional blocks: conceptually-targeted, contentually-procedured and resultantly-evaluated. The conceptually-targeted block includes the purpose and objectives of the experimental system, organizational-pedagogical conditions and the principles of its implementation. Contentually-procedured one is the main system’s block, which includes the most components: the stages of experimental system implementation; methods and organizational forms of experimental learning; specific features of linguomethodical education of the future teachers native language as a strategic guideline for linguomethodical pedagogics in the university; the structure of a linguomethodical competence and linguomethodical culture of primary school future teachers; an author’s e-linguomethodical content; the classification of electronic linguomethodical tools for primary school and for high school; the classification of electronic linguomethodical tools technical providing; the criterion of quality evaluation of primary school electronic products. The resultantly-evaluated block is final in the experimental system and includes: the components of the future elementary school teachers readiness to use the electronic linguomethodical tools in their professional activities; the measuring criteria for each components; the criteria indicators for measuring disclosure; the levels of the readiness to use the electronic linguomethodical tools in professional activities; the result of the implementation of the proposed system. Revealing the structure of each block, the author describes its components, and we can really understand the content, structure, organizational ways and methods of the proposed experimental system implementation.